Principal Ideal Theorem of Modul - SULASTRI T (NIM: 20114045), EVI
Principal Ideal Theorem is one of the cornerstone of the dimension theory for Noetherian rings. For an R-module M, certain submodules of M analogue to that of prime ideal in the ring R. Using this definition, we extend principal ideal theorem of Noetherian Rings to modules over locally a unique factorization domain.